Creative Catechesis: A Creative and Psychosocial Approach to Faith Formation, A Source Book for Today's Catechesis - Dharma, Journal of (Journal of Dharma, 2001)
Dr, Anto Amarnad cmi, Creative Catechesis: A Creative and Psychosocial Approach to Faith Formation, A Source Book for Today's Catechesis, Bangalore: Dharmaram Publications, 2000, pp. iv+300. Rs. 160.00, US$ 18.00. ISBN: 81-86861-25-4.